Polyethylene Glycol (PEG)-Assisted Axonal Fusion in the Surgical Management of Brachial Plexus Injury: A Novel Clinical Methodology - Sharma, Aparna; Kaul, Rakshay; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Traumatic brachial plexus injury (BPI) often results in severe functional impairment due to the extensive distance required for axonal regeneration and the limited regenerative rate (∼1–3 mm/day). Traditional surgical strategies, including nerve grafts and transfers, often fail to deliver optimal outcomes, especially in pan-plexus or proximal injuries, due to delayed reinnervation and irreversible muscle atrophy.This article develops and describes a novel surgical protocol integrating polyethylene glycol (PEG)-assisted axonal fusion with conventional nerve transfer techniques for improved functional recovery in patients with traumatic BPI.This single-center, prospective clinical study enrolled adult patients with partial or complete traumatic BPI. After detailed neurological and radiological assessment, patients underwent nerve transfer procedures (e.g., spinal accessory nerve [SAN]–suprascapular nerve, SAN to musculocutaneous nerve [MCN] using sural nerve Oberlin, intercostal nerve–MCN), during which 50% PEG solution was applied at the coaptation site following the Bittner fusion sequence. Intraoperative steps included hypotonic and calcium-free saline preparation, methylene blue staining of nerve ends, PEG application, and final calcium-enhanced saline rinse. Patients were followed for 6 months with regular assessments of motor and sensory recovery, electromyography/nerve conduction studies, and patient-reported outcomes.PEG-assisted fusion is hypothesized to prevent Wallerian degeneration, promote immediate axonal continuity, accelerate muscle reinnervation, and enhance both motor and sensory recovery compared to conventional methods alone.This study introduces the first PEG-fusion protocol adapted for BPI repair in humans. By combining established microsurgical techniques with a biophysical approach to nerve continuity restoration, this methodology holds promise for improving recovery timelines and functional outcomes in BPI patients.
Keywords: brachial plexus injury; polyethylene glycol; nerve fusion; axonal regeneration; nerve transfer; peripheral nerve repair